Agronomic biofortification of rice and wheat with zinc: A metanalytical study (Research, Society and Development, 2021)
A diet based on cereals may lack essential mineral elements, among them zinc. The provision of this element in diets can be via supplements, food fortifiers or agronomic biofortification (AB), a practice adopted on a farmer scale. It was carried out different studies in countries with specific local conditions. The meta-analysis allows combining quantitative results from different studies, providing a synthesis of results with high reliability. The objective of this work was to analyze the response of rice (Oryza spp.) and wheat (Triticum spp.) to fertilization with zinc in terms of grain yield and accumulation of this nutrient in the grain. We carried out a systematic review where 16 scientific articles from the last five years were selected, and 179 studies fitted the established criteria. The effect size for Zn application via leaf or soil in rice and wheat compared to the control was calculated using the natural logarithm (lnR) between the ratio of the treatment group and the control group for both variables. Agronomic biofortification with Zn increases grain yield (7%) and zinc content in grains (53%). These results depend on plant species and the fertilization way (via the soil or foliar spray).  Agronomic Biofortification may be a valuable strategy to combat malnutrition and guarantee food sovereignty.